Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan di PT. Exim Jaya Abadi (AsiaCommerce Network Ltd) - Davit Nur Fajar; Musthafa Kamil (Universitas 17 Agustus 1945 Semarang, 2024)
Employee performance is crucial for companies to achieve their goals and grow. This study investigates the impact of compensation and work environment on employee performance at PT. Exim Jaya Abadi. Data was collected through questionnaires and secondary sources. Data analysis included quality tests, classical assumption tests, regression analysis, hypothesis testing, and coefficient of determination tests. The results showed that compensation has a positive effect on employee performance (t count 5.564 > t table 2.00958, significant 0.000 < 0.05). Conversely, the work environment has a negative effect on employee performance (t count -2.162 > t table 2.00958, significant 0.036 < 0.05). Simultaneously, compensation and work environment affect employee performance (F count 29.921 > F table 3.18, significant 0.000 < 0.05). An Adjusted R Square of 0.531 indicates that 53.1% of the variation in employee performance is influenced by compensation and work environment, while 46.9% is influenced by other factors not discussed in this study.